2018
DOI: 10.1111/codi.14322
|View full text |Cite
|
Sign up to set email alerts
|

Perirenal fat surface area as a risk factor for perioperative difficulties and 30‐day postoperative complications in elective colon cancer surgery

Abstract: PRF, an easily measured indirect marker of visceral obesity, was associated with overall and moderate complications in men and women and could serve as a useful tool in the assessment of preoperative risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…21,45 From a technical perspective, greater abdominal adiposity has been associated with longer operation time and higher blood loss, increasing patients' risk of having complications, 21 all of which could contribute to risk of complication, readmission, or prolonged LOS. [46][47][48][49][50] Although preoperative therapy is increasingly recognized as an essential component of surgical care, 51 to our knowledge, only few physical and nutritional intervention studies have been conducted before CRC surgery. 52,53 In fact, the systematic review of these studies has not shown a significant reduction in postoperative complications or LOS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,45 From a technical perspective, greater abdominal adiposity has been associated with longer operation time and higher blood loss, increasing patients' risk of having complications, 21 all of which could contribute to risk of complication, readmission, or prolonged LOS. [46][47][48][49][50] Although preoperative therapy is increasingly recognized as an essential component of surgical care, 51 to our knowledge, only few physical and nutritional intervention studies have been conducted before CRC surgery. 52,53 In fact, the systematic review of these studies has not shown a significant reduction in postoperative complications or LOS.…”
Section: Discussionmentioning
confidence: 99%
“…Acting as a metabolic organ, adipose tissue participates in the inflammatory process by secreting a variety of cytokines that potentially inhibit the healing process and promote infection following surgery . From a technical perspective, greater abdominal adiposity has been associated with longer operation time and higher blood loss, increasing patients’ risk of having complications, all of which could contribute to risk of complication, readmission, or prolonged LOS …”
Section: Discussionmentioning
confidence: 99%
“…[21] Jung et al [1] showed that perirenal fat surface area has a higher predictive value for postoperative outcomes in colorectal surgery than BMI and waist-to-hip ratio. der Hagopian et al [22] reported in their study that perirenal fat surface area, which is an indirect marker of visceral obesity, is associated with complications and can serve as a useful tool for preoperative risk assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Perirenal fat, measured using CT images, has been reported 11–13 as an easily reproducible, indirect measurement that correlates with visceral fat. These studies found an association between the volume of perirenal fat and postoperative complications after colorectal surgery, but this association has not been investigated in surgery for gastric cancer.…”
Section: Introductionmentioning
confidence: 99%